Associations of Carbohydrate Intake With New-Onset Hypertension Subtypes: Results From the China Health and Nutrition Survey (2000–2011) - Qi, Su-Fen; Cao, Ya-Jing; Wang, Hui-Jun; Zhang, Bing; Yan, Jing; Tian, Qing-Bao (Frontiers in Nutrition, 2022)
Background: The effects of carbohydrate intake on hypertension (HTN) subtypes are scarce. We examined the association of carbohydrate intake with new-onset HTN subtypes in Chinese adults. Methods: Chinese Health and Nutrition Survey (CHNS) 2000–2011, 22,418 individuals were recorded using a 24-hour recall method over three consecutive days. We excluded those who were pregnant women, lactating mothers, age <18 years, baseline age, blood pressure, and energy intake deficiency, extreme energy intake (male > 6000 kcal or < 800 kcal; female > 4000 kcal or < 600 kcal), and pulse pressure difference (Systolic Blood Pressure [SBP] - Diastolic Blood Pressure [DBP]) <10 mm Hg, HTN at baseline and data from only one survey. The total number of subjects who participated in at least two surveys was 7,930. The main outcome was new-onset HTN subtypes over 6.9 person years of follow-up. Results: 2,521 participants were found to be HTN, which included 1,318 males (52.3%), 1,203 females (47.7%), 721 had SDH (28.6%), 655 had ISH (26.0%) and 993 had IDH (39.4%). Compared with extreme quintiles of carbohydrate, multivariable-adjusted hazard ratios (HR) and 95% confidence intervals (CI) for new-onset HTN, SDH, ISH and IDH associated with carbohydrate intake were 1.12 (0.97–1.30), 1.54 (1.18–2.00), 0.89 (0.67–1.19) and 1.15 (0.91–1.45), respectively. The HR of SDH compared with extreme quintiles of carbohydrates was 1.56 (95% CI, 1.08-2.25; P trend=0.04) in men and 1.52 (95% CI, 1.02-2.26; P trend=0.02) in women. Conclusion: Carbohydrates were related to a higher risk of SDH, which were not observed with HTN, ISH and IDH.